European Islam in the Age of Globalisation and Legal Pluralism: Not Easy Being European - Menski, Werner (NAVEIÑ REET: Nordic Journal of Law and Social Research, 2021)
The article argues that polycentric and polyphonic basic principles of pluralist navigation are always needed as balancing tools to preserve sensitivity and awareness of agile agency of various legal, social and religious stakeholders to allow situation-specific forms of navigation. Clearly, this does not mean that ‘anything goes’, but demands that complex hybrid solutions have to be sought. Obviously states must retain a right to determine responsibly how their respective national identity and legal order should develop in conditions, nowadays, of intense pluralist challenges posed by increasingly diverse demographic structures. Especially the presence of many people in the Nordic countries who are Muslims, may have strong links to other legal orders, and feel connected to a religion that they value as part of their own life and identity while also claiming the right to be Danish, Finnish, Norwegian or Swedish, cannot be ignored.